Understanding UK farmers' Brexit voting decision: A behavioural approach. (January 2021) - May, Daniel; Arancibia, Sara; Manning, Louise
Abstract: In spite of the potential negative effects that Brexit could bring to the United Kingdom (UK), the majority of the electorate voted to leave the European Union (EU). As a result of this paradoxical choice, a number of studies have been developed to understand the factors that triggered this voting decision. Most of them take into account factors related to immigration from East Europe, national identity, and sovereignty recovering, among others. However, these factors do not seem to reflect the reasons behind farmers' Brexit voting choice. Using a behavioural approach based on the theory of planned behaviour, the aim of the study was to contribute to the body of literature by undertaking an indicative study of UK farmers' Brexit voting decisions. The study found that for the sample group, voting choice was strongly influenced by farmers' perceptions about EU legislation, their attitudes towards the EU, their perceived capacity to control factors that impact on the farm performance, their sense of self and their notions of autonomy within the confines of prescriptive agricultural policy and the influence of their social relationships. Highlights: Geographic location influenced voting preference. Type of farm enterprise and farm size influence voting preference. Attitude towards the EU had the highest predictive power of voting intention. Farmers with greater social relationships more likely to vote to remain in EU.